EFFECTS OF HUMIC ACIDS ON POULTRY UNDER STRESS CONDITIONS - Janka Vaskova; Peter Patlevič; Daniel Žatko; Slavomír Marcinčák; Ladislav Vaško; Klára Krempaská; Jozef Nagy (Slovenian Veterinary Research, 2018)
The transportation of chickens from the poultry farm to the slaughterhouse causes stress conditions that influence the oxidative status of the whole organism and subsequently change the organoleptic properties of the meat delivered to the consumer. The aim of this work was to investigate how administering 0.6% humic acids to broiler chickens for a period of 42 days affects the level of selected enzymes directly involved in oxidative stress elimination. For the most objective estimation of the oxidative state, parameters were determined in liver and kidney mitochondria, and in the blood plasma. With regards to the chelating properties of humic acids, our interest was in monitoring the effects on the distribution of the transition metals Fe, Zn, Cu, Mn, which serve as cofactors of antioxidant enzymes. We have found that, under normal conditions, 42 days of humic acid administration do not cause significant metal redistribution. It has a significant effect on Se excretion, according to the pronounced deposition of Se in kidney tissue, without significantly increased activity of the corresponding enzyme. This led to compensation by changes in other antioxidant enzyme activities. This is a noteworthy finding, especially after administration of longer than 42 days. In conditions caused by sudden stress, according to the detected element levels, it is possible to expect a better response in the case of humic acid administration. The effect of humic acid supplementation appeared to be organ-specific and may ultimately be beneficial for the chickens' health, stress elimination and, finally, the quality of the meat. Key words: antioxidant enzymes; humic acids; chicken; metal cofactors; oxidative stress